2014
DOI: 10.1002/ange.201309767
|View full text |Cite
|
Sign up to set email alerts
|

Der elektronische Grundzustand von [Fe(CO)3(NO)]: eine spektroskopische und theoretische Studie

Abstract: Fe‐katalysierte Reaktionen haben sich in den vergangenen 10 Jahren fest in der organischen Synthese etabliert. Das ursprünglich von Hogsed und Hieber beschriebene komplexe Ferrat [Fe(CO)3(NO)]− zeigt katalytische Aktivität in zahlreichen organischen Reaktionen und wird allgemein als isoelektronisch zum [Fe(CO)4]2− betrachtet. Allerdings zeigt der letztgenannte Komplex kaum katalytische Aktivität. Die hier vorgestellten spektroskopischen und quantenchemischen Untersuchungen zeigen, dass das komplexe Ferrat [Fe(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
17
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 60 publications
3
17
0
2
Order By: Relevance
“…[3] However, from a fundamental perspective, the long-known flexible bonding motifs and bonding fashions of the NO ligand [4] are still under discussion and reinvestigation today. [5] And as much as the chemistry of Fe II and Fe III is well established, as much is yet to learn about the chemistry of iron in the unusual oxidation state of + I. The synthesis of such compounds is mainly achieved by the reduction of Fe II precursors, usually stabilized by bulky strong donor ligands such as [C{Si(CH 3 ) 3 } 3 ] À , [6] cyclic (alkyl)-(amino)carbenes [7] or N-heterocyclic carbenes (NHCs).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[3] However, from a fundamental perspective, the long-known flexible bonding motifs and bonding fashions of the NO ligand [4] are still under discussion and reinvestigation today. [5] And as much as the chemistry of Fe II and Fe III is well established, as much is yet to learn about the chemistry of iron in the unusual oxidation state of + I. The synthesis of such compounds is mainly achieved by the reduction of Fe II precursors, usually stabilized by bulky strong donor ligands such as [C{Si(CH 3 ) 3 } 3 ] À , [6] cyclic (alkyl)-(amino)carbenes [7] or N-heterocyclic carbenes (NHCs).…”
mentioning
confidence: 99%
“…[8] But especially in the absence of those strong and sterically demanding ligands, an undisturbed insight to iron(I) systems is scarce. With that in mind, we made use of the versatility of carbon monoxide (CO) as a ligand by starting from Fe(CO) 5 as a Fe 0 source in combination with an oxidative approach. In order to compensate for the lability of the Fe À CO bond in the resulting iron cations, we utilized the weakly coordinating anion (WCA) [F-{Al(OR F ) 3 } 2 ] À (R F = C(CF 3 ) 3 ) [9,10] [11] In regard to ternary carbonyl/nitrosyl cations, the only currently known examples are [Cr(CO) 5 -(NO)][WCA], reported by us [12] and [Co(CO) 2 (NO) 2 ]-[WCA].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[ [11] Weiterhin reichen fürd as berühmte [Fe(H 2 O) 5 NO)] 2+ -Kation die postulierten Oxidationsstufen von Fe I (NO + )z uF e III (NO À ). [ [11] Weiterhin reichen fürd as berühmte [Fe(H 2 O) 5 NO)] 2+ -Kation die postulierten Oxidationsstufen von Fe I (NO + )z uF e III (NO À ).…”
unclassified
“…[37] On the basis of the ambivalent nature of NO ligands, the actual oxidation state of iron in complex 46 may be as high as iron(III). Plietker found that complex 46 efficiently catalysed the addition of both aromatic and aliphatic thiols 47 to a,b-unsaturated ketones 48 and nitriles.…”
Section: (No)]mentioning
confidence: 99%